PENCAHAYAAN KANDANG SAPI DI PETERNAKAN SAWALAKSA BUANA DESA CIMAUNG, JAWA BARAT - Endah Setyaningsih; Yohanes Calvinus; Hadian Satria Utama; Alfina Putri Mulyo (Jurnal Bakti Masyarakat Indonesia, 2021)
Sawalaksa Buana Farm was established in 2015, in Cimaung village, West Java. The area is about 1200 m2, there are two cages in the area. The first cage was used as a feedlot with a capacity of 24 bulls. The second cage, used as a cow shed for breeding, has a capacity of 20 cows. Another area is a cattle feed warehouse and a fermentation area for making feed. Cow food is the result of processing corn stalk waste by fermentation, and the Sawalaksa Buana farm produces this food. Corn stalk waste is obtained from farmers around the farm. The lighting system in the enclosure and the surrounding environment uses LED bulbs, 28 watts of power. Installation of lights in the area around the cage without using a lamp housing, both for the inside and outside/the environment. In accordance with the shape of this LED lamp, its use is more appropriate for the inside of the room, but in this farm, besides being used for the cage area, it is also used for the outside, namely the environment and around the road. The partners' problems are lack of understanding in the selection and placement of LED lights, already using LED lights, but lack of detailed specifications, selection of shapes and lamp housings that are not appropriate for lighting around the cage and for the area around the road. The solution offered is in the form of retrofitting lights on the cowshed and its environment to optimize the use of LED lights and lamp housings. The method of implementing PKM is in the form of field surveys, analyzing and replacing lamps and lamp houses in cattle pens and their environment. The results obtained from the lighting of the cage can be optimized, namely by using the type of lamp according to its designation, the use of the lamp housing and the selection of the appropriate lamp power. Thus, the purpose of implementing this PKM can be fulfilled.ABSTRAK:Peternakan Sawalaksa Buana berdiri tahun 2015, di desa Cimaung, Jawa Barat. Luas area sekitar 1200 m2, terdapat dua kandang di area tersebut.  Kandang pertama dipakai sebagai kandang penggemukan berkasipasitas 24 ekor sapi jantan. Kandang kedua, dimanfaatkan sebagai kandang sapi betina untuk pembibitan/breeding, berkapasitas 20 ekor sapi betina. Area lain berupa gudang makanan sapi dan area fermentasi pembuatan pakan. Makanan sapi berupa hasil pengolahan limbah batang jagung dengan cara difermentasi, dan makanan ini diproduksi sendiri oleh peternakan Sawalaksa Buana. Limbah batang jagung diperoleh dari petani sekitar peternakan. Sistem pencahayaan pada kandang dan lingkungan sekitarnya menggunakan lampu bohlam LED, daya 28 watt. Pemasangan lampu pada area sekitar kandang tanpa menggunakan rumah lampu, baik untuk bagian dalam dan luar/lingkungan. Sesuai dengan bentuk lampu LED ini, penggunaannya lebih tepat untuk ruangan bagian dalam, namun di peternakan ini, selain digunakan untuk area kandang, juga untuk bagian luar yaitu lingkungan dan sekitar jalan. Permasalahan mitra adalah kurang paham dalam pemilihan dan penempatan lampu LED, sudah menggunakan lampu LED, namun spesifikasi kurang detil, pemilihan bentuk dan rumah lampu yang kurang tepat untuk pencahayaaan sekitar kandang dan untuk area sekitar jalan. Solusi yang ditawarkan berupa retrofit lampu pada kandang sapi dan lingkungannya untuk mengoptimalkan penggunaan lampu LED dan rumah lampu. Metode pelaksanaan PKM berupa survei lapangan, menganalisis dan penggantian lampu dan rumah lampu pada kandang sapi dan lingkungannya. Hasil yang diperoleh pencahayaan kandang dapat dioptimalkan, yaitu dengan penggunaan jenis lampu sesuai peruntukannya, penggunaan rumah lampu dan pemilihan daya lampu yang sesuai. Dengan demikian tujuan pelaksanaan PKM ini dapat terpenuhi